Pro-Angiogenic Effects of Latent Heparanase and Thrombin Receptor-Mediated Pathways—Do They Share a Common Ground in Melanoma Cells? - Hoß, Sebastian G.; Grundmann, Manuel; Benkel, Tobias; Gockel, Lukas; Schwarz, Svenja; Kostenis, Evi; Schlesinger, Martin; Ilan, Neta; Vlodavsky, Israel; Bendas, Gerd (Thrombosis and Haemostasis, 2018)
Heparanase (HPSE) is an endo-β-D-glucuronidase that cleaves heparan sulphate (HS) chains of proteoglycans (HSPGs). Besides a remodelling of the extracellular matrix, HPSE increases the bioavailability of pro-angiogenic mediators, such as HS-associated vascular endothelial growth factor (VEGF), thereby contributing to metastatic niche formation. Notably, HPSE also induces release of VEGF from tumour cells independent of its enzymatic activity, but the underlying molecular mechanisms remain unresolved. We found that exogenous addition of latent HPSE stimulates VEGF release from human MV3 melanoma cells. The same effect was noted upon direct stimulation of thrombin receptor (protease-activated receptor 1 [PAR-1]) by Thrombin Receptor Activator Peptide 6 (TRAP-6). The matricellular ligand cysteine-rich 61 protein (Cyr61) was identified as pathway component since Cyr61 knockdown in MV3 cells abolished the VEGF release by TRAP-6 and HPSE. Since both TRAP-6 and HPSE mediated an up-regulation of phosphorylated focal adhesion kinase, which could be blocked by antagonizing PAR-1, we postulated a crosstalk between latent HPSE and PAR-1 in promoting pro-angiogenic pathways. To test this hypothesis at a molecular level, we applied dynamic mass redistribution (DMR) technique measuring intracellular mass relocation as consequence of direct receptor activation. Indeed, latent HPSE evoked a concentration-dependent DMR signal in MV3 cells as TRAP-6 did. Both could be modulated by targeting G-protein receptor signalling in general or by the PAR-1 inhibitor RWJ 56110. Using cells devoid of cell surface HS synthesis, we could confirm HPSE effects on PAR-1, independent of HSPG involvement. These data indicate, for the first time, a crosstalk between latent HPSE, thrombin receptor activation and G-protein signalling in general.
Keywords: heparanase; metastatic niche; PAR-1; tumour; vascular endothelial growth factor